2016
DOI: 10.1242/dmm.022251
|View full text |Cite
|
Sign up to set email alerts
|

Cellular dynamics of regeneration reveals role of two distinct Pax7 stem cell populations in larval zebrafish muscle repair

Abstract: Heterogeneity of stem cells or their niches is likely to influence tissue regeneration. Here we reveal stem/precursor cell diversity during wound repair in larval zebrafish somitic body muscle using time-lapse 3D confocal microscopy on reporter lines. Skeletal muscle with incision wounds rapidly regenerates both slow and fast muscle fibre types. A swift immune response is followed by an increase in cells at the wound site, many of which express the muscle stem cell marker Pax7. Pax7+ cells proliferate and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 80 publications
6
59
1
Order By: Relevance
“…In zebrafish larvae, muscle injury by puncture wounds to the ventral myotome induces proliferation of SLCs, differentiation and fusion to repair damaged myofibres (Knappe et al, 2015). Of note, the Pax7 gene is duplicated in zebrafish (Pax7a and Pax7b), and they differ in expression pattern and function: Pax7a-cells participate in repair of the first wave of nascent fibres whereas Pax7b-cells generate larger fibres (Pipalia et al, 2016). The ablation of one population or the other results in deficits in repair suggesting lack of compensation (Pipalia et al, 2016).…”
Section: Strategies For Muscle Regeneration In Different Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish larvae, muscle injury by puncture wounds to the ventral myotome induces proliferation of SLCs, differentiation and fusion to repair damaged myofibres (Knappe et al, 2015). Of note, the Pax7 gene is duplicated in zebrafish (Pax7a and Pax7b), and they differ in expression pattern and function: Pax7a-cells participate in repair of the first wave of nascent fibres whereas Pax7b-cells generate larger fibres (Pipalia et al, 2016). The ablation of one population or the other results in deficits in repair suggesting lack of compensation (Pipalia et al, 2016).…”
Section: Strategies For Muscle Regeneration In Different Organismsmentioning
confidence: 99%
“…Of note, the Pax7 gene is duplicated in zebrafish (Pax7a and Pax7b), and they differ in expression pattern and function: Pax7a-cells participate in repair of the first wave of nascent fibres whereas Pax7b-cells generate larger fibres (Pipalia et al, 2016). The ablation of one population or the other results in deficits in repair suggesting lack of compensation (Pipalia et al, 2016). Similarly, it has been shown in the adult electric fish (S. macrurus) that muscle repair following tail amputation also involves Pax7-positive SLCs, but not myofibre dedifferentiation (Weber et al, 2012).…”
Section: Strategies For Muscle Regeneration In Different Organismsmentioning
confidence: 99%
“…7). Since the body of a zebrafish larva is transparent through all developmental stages, such transgenic fish have been used to visualize the vascular system [108], the central and peripheral nervous systems [109, 110], the regenerating processes of the sensory system and fin [111, 112], the cellular process of muscle wound repair [113], and proteolytic cleavage of the extracellular domain of a membrane protein (Neuregulin) in the motor neurons [114], among others. Also, the transgenic fish were applied to image the activity of specific neuronal populations or endothelial cells by targeted expression of a calcium indicator GCaMP [115, 116].…”
Section: Transposons and Functional Genomicsmentioning
confidence: 99%
“…( E ) Caudal trunk (and the wound epidermis) in HGn21A embryo at 1 dpf [112]. ( F ) Fgf7b-positive muscle cells in gSAIzGFFD164A at 1 dpf [113]. ( G ) Central nervous system and motor neurons in the spinal cord in SAIGFF213A at 1 dpf [114].…”
Section: Figurementioning
confidence: 99%
“…In Drosophila, distinct molecular pathways create founder myoblasts, which initiate fibres, and fusion competent myoblasts, which augment fibre growth (Abmayr and Pavlath, 2012). Our recent analyses of zebrafish muscle repair (Knappe et al, 2015;Pipalia et al, 2016) revealed two Pax7-expressing myoblast subpopulations with similarities to founder and fusion-competent cells (Pipalia et al, 2016). Whether such myoblast diversity underlies fibre formation during development and thereby determines muscle size in vertebrates is unknown.…”
Section: Introductionmentioning
confidence: 99%